Identification of post-digestion angiotensin-I converting enzyme (ACE) inhibitory peptides from soybean protein Isolate: Their production conditions and in silico molecular docking with ACE. (30th May 2021) - Xu, Zhenqiu; Wu, Changping; Sun-Waterhouse, Dongxiao; Zhao, Tiantian; Waterhouse, Geoffrey I.N.; Zhao, Mouming; Su, Guowan
Graphical abstract: Highlights: The peptide fraction obtained exhibited a 10.4 times higher ACE-inhibitory activity than SPIH. Peptides IY, YVVF, LVF, WMY, LVLL and FF might be the main contributors to SPIH's ACE inhibition. 2OC2 as the C-domain receptor was suitable for the selection of ACE inhibitory peptides. The ACE-inhibitory activities of IY and WMY unaltered and increased after SGID, respectively. Abstract: This study attempts to investigate natural angiotensin-I converting enzyme (ACE) inhibitors. Soybean protein isolated (SPI) hydrolysate (SPIH) was prepared by Alcalase from inexpensive SPI, and their ACE inhibitory peptides were obtained via membrane separation, ethanol precipitation and adsorption chromatography enrichment. Activated carbon was more suitable for peptide enrichment than eight macroporous resins. The peptide fraction yielded under optimal conditions (protein-active carbon mass ratio 2:1; adsorption pH 3.0 and time 2 h; desorption time 2 h) exhibited a 10.4 times higher ACE-inhibitory activity than SPIH. Novel peptides IY, YVVF, LVF, WMY, LVLL and FF (hydrophobicity values 10.51–12.87; activity scores 0.2373–0.999) might be the main contributors to SPIH's ACE inhibition. IY had the lowest IC50 (0.53 ± 0.02 μM). YVVF had the greatest affinity (−9.8 kcal/mol) for 2OC2 (ACE's C-domain receptor) via H-bonds. IY and WMY could be potent ACE inhibitors, and their ACE-inhibitory activities unaltered and increased after in vitro gastrointestinal digestion.